Application of Customer Relationship Management in Maintaining Customer Loyalty (Case Study Hotel Melati) - Mariam, Mariam (Yayasan Cendekiawan Digital Indonesia (CEDDI), 2023)
This research aims to address the challenges and implement Customer Relationship Management (CRM) in a web-based budget hotel, Hotel Melati, for online bookings, accessing the latest promotional information, and providing online feedback. The study focuses on exploring the novel aspects of implementing CRM in the context of a budget hotel and its impact on maintaining customer loyalty. The research adopts a mixed-methods approach, utilizing interviews and observations for data collection. The development methodology follows the Waterfall method, encompassing sequential steps of analysis, design, implementation, testing, and maintenance. SWOT analysis is employed to identify strengths, weaknesses, opportunities, and threats. UML is used for the design phase, PHP for coding, and MYSQL as the database. Black box testing is conducted to evaluate the application's performance. The results of the black box testing demonstrate that the implemented application functions effectively. The questionnaire results show a satisfaction rate of 82.17%. Based on the feasibility assessment, the findings suggest that the implemented solution is highly suitable for addressing the identified challenges and maintaining customer loyalty.